SOLVENT-INDUCED AGGREGATION THROUGH PT…PT INTERACTIONS: THEORETICAL STUDY OF THE LUMINESCENT ORGANOPLATINUM(II) TERPYRIDYL COMPLEXES - DJOUAMA, H; COSTUAS, K; BOUTARFAIA, A; HALET, J-F (Courrier du Savoir, 2018)
We report a theoretical study of both the structural and optical properties of phosphorescent square-planar Pt(II) terpyridine complexes, namely [Pt(tpy)(CºC-CºCH)]OTf that exhibit, at high concentrations, an additional emission band at longer wavelength. The complex [Pt(tpy)(CºC-CºCH)]OTf 1 has been found to exist in two forms, a dark-green and a red form; both of which have been structurally characterized and shown to exhibit different crystal-packing arrangements. The geometry optimizations of both the ground state of the considered monomer and different possible trimers have been performed in solution using several density functional theory (DFT) functionals. The UV−visible absorption spectra of the complexes are well rationalized using a vertical time-dependent DFT (TD-DFT) protocol relying on a global hybrid exchange−correlation functional. Le changement remarquable des caractéristiques d'absorption UV-vis induites par des changements dans la composition du solvant peut être considéré comme un type spécial de solvatochromisme.